2017
DOI: 10.3233/jpd-161050
|View full text |Cite
|
Sign up to set email alerts
|

Objective Colonic Dysfunction is Far more Prevalent than Subjective Constipation in Parkinson’s Disease: A Colon Transit and Volume Study

Abstract: Significantly delayed colonic transit time and increased volume were frequent findings in PD patients, and objective dysfunction was considerably more prevalent than subjective constipation symptoms. Also, the prevalence of subjective constipation varied widely depending upon which questionnaire was employed. These findings highlight the need for more research on how to define constipation in PD and also the need for improved understanding of the relationship between subjective symptoms and objective dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
97
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 24 publications
9
97
3
1
Order By: Relevance
“…However, it seems probable that the increased small intestine and colon volumes are directly related to reduced muscle tonus and intestinal motility following vagotomy . In similarity to the differential patterns in colonic SUVs and number of retained ROM, we found that regional colonic volume was only significantly increased in the ascending and transverse colon, whereas PD patients show significant increases in the transverse and rectosigmoid colon …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, it seems probable that the increased small intestine and colon volumes are directly related to reduced muscle tonus and intestinal motility following vagotomy . In similarity to the differential patterns in colonic SUVs and number of retained ROM, we found that regional colonic volume was only significantly increased in the ascending and transverse colon, whereas PD patients show significant increases in the transverse and rectosigmoid colon …”
Section: Discussionsupporting
confidence: 68%
“…Colonic transit time (CTT) was measured using the validated radio‐opaque marker technique (ROM), as described previously . In short, participants ingested one gelatine capsule containing 10 ROMs each morning for 6 days prior to the study date.…”
Section: Methodsmentioning
confidence: 99%
“…Constipation is very common in the prodromal phase of PD and objective colonic dysfunction has been recently ascertained in PD patients [32]. At a molecular level, the presence of synuclein aggregates in colonic biopsies of PD subjects has been widely discussed as a main diagnostic factor for PD prior to the onset of clinical motor features, although providing controversial results [5, 33], and other differential factors, such as decreased intestinal acetylcholinesterase activity, have been reported in early PD [34].…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD) is currently defined by motor impairments such as resting tremor, bradykinesia, rigidity, and gait disturbance, but nonmotor features including cognitive impairment, hyposmia, anxiety, depression, sleep disturbances, and, prominently, gastrointestinal (GI) dysfunction have been gaining increasing attention and have a profound impact on quality of life. Constipation is reported by approximately 50% of PD patients and can be detected by objective measures in nearly 80% . It frequently precedes the onset of motor symptoms by more than 15 years .…”
mentioning
confidence: 99%